Thermal characterization of Bacillus subtilis endospores and a comparative study of their resistance to high temperature pulsed electric fields (HTPEF) and thermal-only treatments. (March 2017) - Cregenzán-Alberti, O.; Arroyo, C.; Dorozko, A.; Whyte, P.; Lyng, J.G.
Abstract: Heat characterization of Bacillus subtilis DSM 618 endospores at temperatures ranging from 90 to 120 °C was performed in water and reconstituted skimmed milk. D T values showed that B. subtilis endospores were more heat resistant in skimmed milk than in water and the calculated z -values indicated the same thermo-dependency regardless of the treatment medium used. Moreover, the effect of High-Temperature Pulsed Electric Fields (HTPEF) treatments on the inactivation of B. subtilis endospores in water and its comparison to thermal-only treatments by means of equal F T values at different temperatures was studied. HTPEF treatment consisted in bipolar square-wave pulses (10 μs, 38 kV/cm, 466 Hz) at maximum processing temperatures up to c . 123 °C. Inactivation values greater than c . 4.5 log10 cycles were obtained for both HTPEF and heat treatments with no significant differences between them. However, further studies at higher electric field strengths and temperatures could be performed to establish if greater inactivation levels can be achieved and to observe whether PEF has an additional effect over heat. Highlights: B. subtilis endospores were more heat tolerant in milk than in water. z -values for B. subtilis spores in milk and water were not significantly different. HTPEF inactivated more than 4.5 log10 cycles of B. subtilis spores. HTPEF offered no advantage to heat using the conditions applied.